2013
DOI: 10.3354/dao02678
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for cardiomyopathy syndrome (CMS) in Norwegian salmon farming

Abstract: Cardiomyopathy syndrome (CMS) has been an economically important disease in Norwegian aquaculture since the 1990s. In this study, data on monthly production characteristics and case registrations were combined in a cohort study and supplemented with a questionnairebased case-control survey on management factors in order to identify risk factors for CMS. The cohort study included cases and controls from 2005 to 2012. From this dataset differences between all cases and controls were analyzed by a mixed effect mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 19 publications
1
30
0
Order By: Relevance
“…Thus far, CMS outbreaks have only been observed in Atlantic salmon after transfer to sea, typically occurring during the second year of the seawater phase. In a study including all Norwegian salmon cohorts from 2004 to 2012, the median time from sea transfer to diagnoses of CMS was 16 months, with an interquartile range of 13–19 months and an average fish weight of 3.6 kg (Bang Jensen, Brun, Fineid, Larssen, & Kristoffersen, ). Cases of CMS have also been reported from fish groups as early as five to 6 months after sea transfer (Fritsvold et al., ; Wiik‐Nielsen et al., ).…”
Section: Epidemiologymentioning
confidence: 99%
See 3 more Smart Citations
“…Thus far, CMS outbreaks have only been observed in Atlantic salmon after transfer to sea, typically occurring during the second year of the seawater phase. In a study including all Norwegian salmon cohorts from 2004 to 2012, the median time from sea transfer to diagnoses of CMS was 16 months, with an interquartile range of 13–19 months and an average fish weight of 3.6 kg (Bang Jensen, Brun, Fineid, Larssen, & Kristoffersen, ). Cases of CMS have also been reported from fish groups as early as five to 6 months after sea transfer (Fritsvold et al., ; Wiik‐Nielsen et al., ).…”
Section: Epidemiologymentioning
confidence: 99%
“…In the above‐mentioned study (Bang Jensen et al., ), altogether 371 (16%) of the 2285 registered cohorts were diagnosed with CMS, and a study from 2003 found CMS registered in 14.6% of the spring smolt and 13.3% of the fall smolt groups, which were followed from sea entry until slaughter (Brun et al., ). As for seasonal variations, these are reported to be slight, although with an increase in cases in fall and spring (Kongtorp et al., ).…”
Section: Epidemiologymentioning
confidence: 99%
See 2 more Smart Citations
“…(7) Infection pressure: Infection pressure was defined as exposure to infection by proximate infectious farms. Different scenarios for infection pressure were tested (see Bang Jensen et al 2013) with the following formula:…”
Section: Independent Variablesmentioning
confidence: 99%